STORYTELLING METHODS FOR EARLY CHILDHOOD RECEPTIVE LANGUAGE - Evarastina Mattemmu; Arismunandar; Rusmayadi; Wahira; Herlina (Media Inovasi Pendidikan dan Publikasi, 2026)
Storytelling with two-way interaction improves receptive language Storytelling that allows children to retell or discuss has been shown to improve understanding of language structure and vocabulary. The purpose of this study is to determine the effectiveness, influences of differences and obstacles of conventional storytelling methods, such as Kamishibai, in improving receptive language skills in early childhood. This research method uses a quasi-experimental design with a quantitative approach. This study uses quantitative data because it aims to measure the influence of storytelling methods on early childhood receptive language skills. Quantitative data was obtained in the form of numbers and scores from tests or observation sheets used to assess children's receptive language skills before and after treatment. The data analysis technique used is Structural Equation Modeling (SEM) based on Partial Least Squares using SmartPLS 4 software, which allows simultaneous analysis of measurement and structural models. The results showed that conventional storytelling methods showed a significant improvement in the receptive language skills of children aged 5-6 years., the application of digital storytelling in educational institutions aged 5-6 years resulted in a strong correlation (r=0.668, p<0.05) with the development of receptive language, digital storytelling was more effective than conventional because of dynamic visual-audio integration that strengthened receptive processing., The main barriers to digital storytelling include limitations infrastructure (such as devices and internet in rural kindergartens) and low teacher digital competence, causing only 40-50% of institutions to be able to implement it optimally.., Teachers' digital competence and infrastructure are key factors because they determine the quality of story delivery. This study makes an original contribution with a direct comparison of digital vs. conventional storytelling in the receptive language of children 5-6 years old who are rarely done simultaneously in a quasi-experimental study.